2000
DOI: 10.1021/ic000314n
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Coupling through the Carbon Skeleton of Malonate in Two Polymorphs of {[Cu(bpy)(H2O)][Cu(bpy)(mal)(H2O)]}(ClO4)2 (H2mal = Malonic Acid; bpy = 2,2‘-Bipyridine)

Abstract: Two polymorphic malonato-bridged copper(II) complexes of formula ([Cu(bpy)(H2O)][Cu(bpy)(mal)(H2O)])-(ClO4)2 (1 and 2) (bpy = 2,2'-bipyridine and mal = malonate dianion) have been prepared and their structures solved by X-ray diffraction methods. Compound 1 crystallizes in the monoclinic space group P2(1)/a, with a = 23.743(3) A, b = 9.7522(5) A, c = 27.731(2) A, beta = 114.580(10) degrees, and Z = 4. Compound 2 crystallizes in the orthorhombic space group Pbcn, with a = 23.700(5) A, b = 25.162(5) A, c = 9.693… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(59 citation statements)
references
References 48 publications
1
58
0
Order By: Relevance
“…[8b,9] The few examples involving the antianti mode indicated that this coupling is weakly ferromagnetic or antiferromagnetic. [9,25] Coupling J 1 arises from the double syn-syn carboxyl bridge and gives a weak antiferromagnetic coupling in this case, but coupling J 3 through the single anti-anti carboxyl bridge gives very weak ferromagnetic coupling. The J 1 value is larger than the J 3 value, which shows that the syn-syn carboxyl bridge is more favorable than the anti-anti mode for transmission of the magnetic coupling interaction.…”
Section: Magnetic Propertiesmentioning
confidence: 91%
“…[8b,9] The few examples involving the antianti mode indicated that this coupling is weakly ferromagnetic or antiferromagnetic. [9,25] Coupling J 1 arises from the double syn-syn carboxyl bridge and gives a weak antiferromagnetic coupling in this case, but coupling J 3 through the single anti-anti carboxyl bridge gives very weak ferromagnetic coupling. The J 1 value is larger than the J 3 value, which shows that the syn-syn carboxyl bridge is more favorable than the anti-anti mode for transmission of the magnetic coupling interaction.…”
Section: Magnetic Propertiesmentioning
confidence: 91%
“…The malonate ligand, with two neighbouring carboxylate groups, is a very flexible bridging ligand [2][3][4][5][6][7], because it can adopt several chelating bidentate coordination modes (bidentate chelation, bidentate chelation-unidentate, bidentate chelation-bis (unidentate)) and different carboxylatobridging coordination modes (syn-syn, syn-anti, and antianti) [6]. On the other hand, the malonate ligand occupies one or two coordination positions, allowing the inclusion of other ligands in the coordination sphere of the metal.…”
Section: Introductionmentioning
confidence: 99%
“…Malonate ligands are potentially useful stabilizing ligands for precursor synthesis and their potential has rarely been explored, except for a few examples. [7,8] Malonate ligands are better electron donors and it was anticipated that homoleptic malonate ligands would provide better stability to the resulting complex compared to heteroleptic b-ketoester ligands. In addition, sterically bulky tert-butoxy groups are expected to provide the necessary shielding of the metal center, and at the same time they would act as cleavage points inducing facile thermal decomposition.…”
Section: Introductionmentioning
confidence: 99%